THE DEVELOPMENT OF MEMBRANOUS PATHOLOGY OF HEPATOCYTES THE INFLUENCE OF INTOXICATION - I.Yu. Bagmut; I.L. Kolisnyk; A.V. Titkova; Yu.K. Rezunenko; O.D. Boiagina (Проблеми екології та медицини)
The study was performed at the Department of Clinical Pathophysiology, Topographical Anatomy and Operative Surgery at Kharkiv Medical Academy of Postgraduate Education as a part of research project "Radiotoxins' pathochemical mechanisms and methods of early diagnostics and correction", state registration No. 0117U000589.